2017
DOI: 10.5751/es-09042-220140
|View full text |Cite
|
Sign up to set email alerts
|

Collective action to save the ancient temperate rainforest: social networks and environmental activism in Clayoquot Sound

Abstract: ABSTRACT. In 1993 over 850 people were arrested for engaging in civil disobedience to prevent the clear-cut logging of pristine ancient temperate rainforests in Clayoquot Sound, Canada. This was the largest incident of this type in Canadian history, and has arguably been Canada's most visible mobilization over a specific environmental issue. This study examines the factors that explain the ongoing participation of individuals in the environmental movement (more broadly, beyond participation in civil disobedien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Preexisting ties and structural proximity to movement members have become somewhat synonymous with consensus building and value‐alignment (McAdam and Paulsen ). People participate in environmental protests due to identification with the movement, a high‐level of communication with environmental networks, and the number of environmental organizations they are tied to (ego‐network centrality) (Tindall and Robinson ). Social network structures can also be an outcome of environmental activism (Tindall, Cormier, and Diani ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Preexisting ties and structural proximity to movement members have become somewhat synonymous with consensus building and value‐alignment (McAdam and Paulsen ). People participate in environmental protests due to identification with the movement, a high‐level of communication with environmental networks, and the number of environmental organizations they are tied to (ego‐network centrality) (Tindall and Robinson ). Social network structures can also be an outcome of environmental activism (Tindall, Cormier, and Diani ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through the analysis of this rich body of data, they provide a detailed description of the patterns of interaction and information flows between local and regional actors, and highlight key factors potentially shaping actors' behaviors or impeding behavioral change, such as social pressure. Tindall and Robinson (2017) studied the personal networks of environmental activists engaged with the protection of the Clayoquot Sound forest area, Canada. They grounded their work on previous studies that have shown that interpersonal connections play a key role in explaining the participation of individuals in social movements: The more connections an individual has to activists, the more likely it is that he/she will become involved him/herself.…”
Section: Sna: Primary Concepts and Methodsmentioning
confidence: 99%
“…The environmental movement has been one of the most important social movements of recent decades (Castells 1997). In Canada, the British Columbia environmental movement has been Canada’s largest and most significant (Tindall and Robinson 2017). In the 1980s and 1990s, there was significant mobilization by environmentalists against clear-cut logging, to protect old-growth forests, biodiversity, and preserve the remaining areas of wilderness (Tindall and Begoray 1993; Wilson 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, if nonactivists have similar patterns of in-movement ties, do other characteristics of their personal networks explain their lack of participation (perhaps contending movement ties or extra-movement ties)? Because of the restricted nature of the samples that have typically been obtained for this line of research (and the problem of sampling on the dependent variable), there is little evidence available to answer these questions (one exception regarding the environmental movement is provided by Tindall and Robinson 2017). To address this problem, the current research compares the characteristics of countermovement participants with those of several other groups.…”
Section: Introductionmentioning
confidence: 99%